Perinatal Outcome of Twins Delivered Vaginally in a Tertiary Care Hospital - Ayesha Zulfiqar, Maliha Sadaf, Amina Abbasi, Sabeen Ashraf, Omair Ashraf, Ayesha Zulfiqar, Maliha Sadaf, Amina Abbasi, Sabeen Ashraf, Omair Ashraf (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the perinatal outcome of first and second twin delivered vaginally in terms of frequency of poor APGAR score and NICU admission in the patient at term in a tertiary care health facility. Introduction: This study aims to improve the perinatal outcome of twin pregnancies through awareness of the need for antenatal care, the recommendation of regular antenatal visits, early recognition of complications, and the presence of neonatal intensive care facilities to improve neonatal outcome by knowing the burden of adverse outcomes in our population. Materials and Methods: This is a descriptive study, conducted at the Department of Obstetrics and Gynaecology at DHQ Hospital, Rawalpindi from January 2019 to June 2019. A total of 91 individuals (female pregnant ladies) who delivered twins (Dichorionic Diamniotic) babies through normal vaginally were selected for descriptive study in the Department of Obstetrics and Gynaecology, DHQ hospital Rawalpindi. All consecutive patients admitted in the labour ward with twin pregnancies were included. Before delivery, the fetal wellbeing of both the twins was evaluated also by ultrasonography. Data collection was done by interview schedule from the patients. Data were analyzed using descriptive statistics using SPSS version 17. For all the quantitative variables like age, gestational age and intertwine interval in seconds. Results: Out of 6278 deliveries during the study period, 91 twin births gave a frequency of 15.16/1000 births. Patients' mean age was 30.14+2.64 years, and mean gestational age was 37.47+0.72 weeks. The mean inter twin delivery interval (mins) in the study was 23.74+4.75. Perinatal outcome of first and second twin in terms of frequency of poor APGAR score and NICU admission in a patient at term was 09 (9.9%) and 27 (29.7%), (p<0.001) respectively. Conclusion: The study concludes that there was a high risk of perinatal outcomes in the second twin as compared to the first twin delivered vaginally. Poor Apgar score and neonatal intensive care admission were more so for the second twin.